Application of ultrasound-guided microwave ablation combined with polidocanol injection in benign cystic-solid thyroid nodules and recurrence analysis - Sichen Yang; Dali Huang (Discover Oncology)
Abstract Objective This study is intended to investigate the efficacy of ultrasound-guided microwave ablation (MWA) combined with polyguinol injection in treating benign cystic-solid thyroid nodules and its effect on recurrence rates. Methods A retrospective analysis was conducted on 120 patients with benign cystic-solid thyroid nodules, who were divided into two groups based on different treatment modalities: the control group (60 cases) and the observation group (60 cases). The control group underwent ultrasound-guided MWA combined with anhydrous ethanol sclerotherapy, while the observation group received ultrasound-guided MWA combined with polidocanol sclerotherapy. Treatment efficacy was assessed postoperatively. Serum levels of free triiodothyronine (FT3), free thyroxine (FT4), and thyroid-stimulating hormone (TSH)were measured before and after surgery. Changes in nodule volume and volume reduction rates were compared. The incidence of adverse reactions and recurrence rates were recorded. Results The observation group demonstrated a significantly higher overall treatment efficacy compared to the control group (P < 0.05). There were no significant differences in preoperative and postoperative FT3, FT4, and TSH levels between the two groups, indicating preserved thyroid function. Postoperative thyroid nodule volumes were significantly reduced in both groups compared to pre-treatment values, with the observation group achieving greater reductions than the control group (P < 0.05). The volume reduction rate was also notably higher in the observation group (P < 0.05). Additionally, the observation group experienced a lower incidence of adverse reactions and recurrence compared to the control group (P < 0.05). Conclusion Ultrasound-guided MWA combined with polidocanol injection is more effective in treating benign cystic-solid thyroid nodules. This approach accelerates nodule ablation, significantly reduces nodule size, preserves thyroid function, lowers recurrence rates, and enhances overall safety.